A retrospective study on the etiological factors of orofacial pain in a Malaysian sample - Mustafa, Nazih Shaban; Kashmoola, Muhanad Ali Hamdon; Mustafa Al-Ahmad, Basma Ezzat; Hazman Fansuri, Mardhiah Abidah; Mohamad Jurimi, Nur Hazwani; Kashmoola, Sayfaldeen (Thieme Medical and Scientific Publishers Pvt. Ltd., 2021)
Objective: This study aimed to examine the etiological factors of orofacial pain for patients attending dental clinic at Faculty of Dentistry, International Islamic University Malaysia (IIUM).